Monazite Microstructures and Their Interpretation in Petrochronology - Schulz, Bernhard (Frontiers in Earth Science, 2021)
The phosphate mineral monazite (LREE,Y,Th,Ca,Si)PO4 occurs as an accessory phase in peraluminous granites and Ca-poor meta-psammopelites. Due to negligible common Pb and very low Pb diffusion rates at high temperatures, monazite has received increasing attention in geochronology. As the monazite grain sizes are mostly below 100 µm in upper greenschist to amphibolite facies meta-psammopelites, and rarely exceed 250 µm in granulite facies gneisses and in migmatites, microstructural observation and mineral chemical analysis need the investigation by scanning electron microscope and electron probe microanalyzer, with related routines of automated mineralogy. Not only the microstructural positions, sizes and contours of the grains, but also their internal structures in backscattered electron imaging gray tones, mainly controlled by the Th contents, can be assessed by this approach. Monazite crystallizes mostly euhedral to anhedral with more or less rounded crystal corners. There are transitions from elliptical over amoeboid to strongly emarginated grain shapes. The internal structures of the grains range from single to complex concentric over systematic oszillatory zonations to turbulent and cloudy, all with low to high contrast in backscattered electron imaging gray tones. Fluid-mediated partial alteration and coupled dissolution-reprecipitation can lead to Th-poor and Th-rich rim zones with sharp concave boundaries extending to the interior. Of particular interest is the corona structure with monazite surrounded by apatite and allanite, which is interpreted to result from a replacement during retrogression. The satellite structure with an atoll-like arrangement of small monazites may indicate re-heating after retrogression. Cluster structures with numerous small monazite grains, various aggregation structures and coating suggest nucleation and growth along heating or/and enhanced fluid activity. Microstructures of monazite fluid-mediated alteration, decomposition and replacement are strongly sutured grain boundaries and sponge-like porosity and intergrowth with apatite. Garnet-bearing assemblages allow an independent reconstruction of the pressure-temperature evolution in monazite-bearing meta-psammopelites. This provides additional potential for evaluation of the monazite microstructures, mineral chemistry and Th-U-Pb ages in terms of clockwise and counterclockwise pressure-temperature-time-deformation paths of anatectic melting, metamorphism and polymetamorphism. That way, monazite microstructures serve as unique indicators of tectonic and geodynamic scenarios.